Analisis Peran YouTube Sebagai Media Komunikasi Dakwah Dalam Pengembangan Masyarakat Islam - Dina Alfiana; Waizul Qarni; Muhammad Habibi Siregar (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The purpose of this study is to analyze the role of YouTube as a Da'wah Communication Media in the Development of Islamic Society. Da'wah is the process of changing one's thoughts, behavior and feelings for the better. YouTube is a strategic communication medium for conveying da'wah to the Islamic community today. This type of research is qualitative with data collection methods using library research. The results of the study show that the use of YouTube as a means of da'wah communication is quite helpful in the development of today's Islamic society.